A Single-Center Early Experience of Endoscopic Submucosal Dissection for Gastric Lesions in Thailand - Prasit Mahawongkajit (Gastroenterology Research and Practice)
Endoscopic submucosal dissection (ESD) was also considered a “high risk” at the starting point with skillful endoscopic techniques and terrible complications. Still, it remains challenging yet has become widespread among institutes in many parts of the world. This study is aimed at further investigating the feasibility, efficacy, and safety of ESD of gastric lesions and at evaluating clinical outcomes in early experience. The patient characteristics, postoperative outcomes, and results of histopathological examinations were reviewed retrospectively between January 2017 and May 2019. Thirteen patients’ gastric ESD were included with all of en bloc resections without recurrence. The long duration was related to the large lesion, the upper part of the stomach, and previous treatment. In this study, the ESD procedure of the stomach is a feasible and safe minimally invasive treatment option with organ preservation. It requires training and experience with a learning approach where skill may be improved to prevent unwanted complications.